2015
DOI: 10.1097/mej.0000000000000155
|View full text |Cite
|
Sign up to set email alerts
|

Acute allergic reactions in the emergency department

Abstract: The incidence of ED visits for acute allergic reaction was high compared with other studies, although the majority of cases were mild. Deviations from published guidelines on the treatment of anaphylaxis are common, with rare use of epinephrine and heavy reliance on H1-antihistamines both in the ED and at discharge. This did not seem to result in any measurable impact on mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
3
13
0
1
Order By: Relevance
“… 10 , 14 Radiocontrast agents are the leading cause in at least one hospital-based study in South Korea, and also feature prominently in recent studies from Australia and Canada. 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 Similarly, a recent US report found that radiocontrast agents caused more fatal drug anaphylaxis than penicillin and cephalosporins combined. 6 This suggested that radiocontrast administration may carry a relatively high “per injection” fatality risk compared with these frequently used antibiotics.…”
Section: Fatal Drug Anaphylaxismentioning
confidence: 99%
“… 10 , 14 Radiocontrast agents are the leading cause in at least one hospital-based study in South Korea, and also feature prominently in recent studies from Australia and Canada. 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 Similarly, a recent US report found that radiocontrast agents caused more fatal drug anaphylaxis than penicillin and cephalosporins combined. 6 This suggested that radiocontrast administration may carry a relatively high “per injection” fatality risk compared with these frequently used antibiotics.…”
Section: Fatal Drug Anaphylaxismentioning
confidence: 99%
“…Delayed injection of epinephrine has been reported in yet another large series of anaphylaxis-related fatalities in which only 23 % of the 92 individuals received it before cardiac arrest [ 93 ]. Although epinephrine injection rates remain low in many EDs [ 94 ], use of protocols or order sets can significantly improve injection rates [ 95 ].…”
Section: Introductionmentioning
confidence: 99%
“…In many countries, EAIs are still unavailable [ 94 ]. Where they are available, they remain under-prescribed and under-used; as an example, only 11 % of 261 individuals with a history of confirmed anaphylaxis had used an EAI during their most recent episode, and 52 % reported that they had never received an EAI prescription [ 8 , 105 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the elicitors may vary according to age, sex and geographical area [ 1 , 3 ]. First line treatment of anaphylaxis is adrenaline [ 1 , 12 ], but previous studies have reported that only a low proportion of anaphylaxis patients receive this treatment [ 6 , 9 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The acute onset of anaphylaxis, the variable symptoms and its transient and unpredictable nature may complicate prospective studies. As a consequence most of the current knowledge on anaphylaxis is derived from retrospective or register based studies [ 1 – 4 , 6 12 ]. To our knowledge, only few studies have assessed anaphylaxis prospectively [ 5 , 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%